Tribological properties and anti-wear mechanism of ZnO@graphene core-shell nanoparticles as lubricant additives. (April 2020) - Ren, Baijing; Gao, Liang; BotaoXie; Li, Mengjun; Zhang, Shangda; Zu, guoqing; Ran, Xu
Abstract: Graphene is regarded as a promising, environmentally friendly candidate for lubricant additives. This work presents a coated nanocomposite with hard-core and soft-shell as lubricant nanoadditive. Three morphological ZnO nanoparticles are synthesized as the core to prepare ZnO@graphene core-shell nanoadditives. A four-ball machine is used to evaluate the anti-friction and anti-wear properties. The effects of ZnO morphology and concentration on the tribological behaviors and worn-out appearance are discussed. The compositional variation of wear scar is characterized to explore the possible anti-wear mechanisms. Researches suggest sheet-like ZnO is more ideal morphology, and ZnO@graphene hard core-soft shell nanostructure is more suitable for dynamic friction environment. The synergistic effect can effectively maintain load capacity and stability of lubricating film, exhibiting excellent tribological property. Highlights: A coated nanocomposite with hard core and soft shell is presented as lubricant additives. Three morphological ZnO nanoparticles are synthesized as the core to prepare ZnO@graphene core-shell nanoadditives. The compositional variation of wear scar is characterized to explore the possible anti-wear mechanisms. The synergistic effect can effectively maintain the load capacity and stability of lubricating film.